Caracterização e avaliação da atividade inseticida do óleo essencial de Hyptis marrubioides (Hortelã do Campo) em larvas de Aedes aegypti - Oliveira, Adriene Maria José de (2020)
Aedes aegypti is the mosquito vector of viruses of various diseases and of great epidemiological importance. It is known that these vectors have become resistant to the various insecticides used for their control so far - which imposes the demand for the development of a product that has an effective action on these transmitters. In search of this contribution to human science, the insecticidal effect of the essential oil of Hyptis marrubioides on Aedes aegypti larvae was studied. The vegetable was grown in the garden of medicinal plants. Oil extraction was performed by hydrodistillation technique, using the modified Clevenger apparatus. The essential oil was characterized by gas chromatography coupled with mass spectrometry. A yield of 0.4603 grams was obtained, in which α-thujone and β-thujone were major components of this species. In the biological tests, the larvae were obtained from laboratory cultivation of eggs of the Rockefeller strain, in a greenhouse with chemical oxygen demand. The 50% lethal dose was found to be 0.026 μl/ml, the 90 lethal dose was 0.083 μl/ml and the 99 lethal dose 0.218 μl/ml. The results were promising, since small doses are required to achieve the lethality of the individuals. These results are expected to contribute to the development of further research and control of the transmitting agent of human disease.